PENGEMBANGAN BUKU PELAJARAN KETERAMPILAN MEMBACA DAN MENULIS BAHASA INDONESIA BAGI PENUTUR ASING BERDASARKAN PENDEKATAN PEMBELAJARAN AKTIF - Roding, Miss Aesoh; Nurhadi, Nurhadi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2018)
Abstract(Title: Developing Indonesian Language Reading and Writing Skill Books for Foreign Speakers Based on Active Learning Approach). This study aimed to (1) produce a textbook of Indonesian language reading and writing skills that is appropriately applied to beginner class BIPA learners based on active learning approaches; and (2) to find out the feasibility of the appropriate Indonesian language reading and writing textbooks applied to BIPA intermediate class learners based on active learning approach. This research was a development research using Borg and Gall development procedure. The steps taken in this research were: (1) preliminary study by observation and interview, (2) product design planning, covering: cover of book, introduction, table of contents, and contents of books, (3) validation of product design conducted by means of validation by experts ie learning BIPA by assessing the content feasibility aspects, language feasibility, feasibility of presentation, and graphic feasibility, (4) product improvement, and (5) the final product that is producing textbook reading and writing skills of Indonesian language for foreign speakers based on an active learning approach. The feasibility instrument used a rating scale with a scale of 1-5. The result of this research and development was a product of Indonesian language reading and writing skill book for foreign speakers based on active learning approach. The quality of Indonesian language reading and writing skills books for foreign speakers based on active learning developed in this study according to experts was high or feasible on the content.Keywords: textbook, reading and writing, BIPA, active learning.